DNA barcoding revises a misidentification on mossy frog: new record and distribution extension of Theloderma corticale Boulenger, 1903 (Amphibia: Anura: Rhacophoridae). (17th February 2018) - Huang, Huayuan; Chen, Zening; Wei, Zhonghui; Bu, Rongping; Wu, Zhengjun
Abstract: As an endangered animal group, mossy frog (genus Theloderma ) has attracted the attention of biologists and wildlife conservationists. Clarifying the taxonomic status and distribution of each species in Theloderma is important to determine the conservation status for each species, establish appropriate conservation strategies and probe the speciation process. Recently, we discovered a medium-sized species of mossy frog of the genus Theloderma in April 2015 during municipal surveys of amphibians in Dayao Mountain of Jinxiu. It was collected from the water-filled tree cavities. However, there remains some uncertainty about the species determination of the mossy frog in the Yinshan station of Dayao Mountain in Guangxi Province, China. Previously, the mossy frog in Guangxi Province was recognized as Th. kwangsiense . In order to clarify the species status of the mossy frog obtained from Guangxi, we sequenced 2414 bp of the 12S and 16S genes in the sample collected from the Dayao Mountain. Combining all the sequence in NCBI, genetic analyses from the data suggest that the sample from the Dayao Mountain is Th. corticale rather than Th. kwangsiense . It is most likely that the most previous studies had wrong species identification. And, it is the first time we use DNA barcoding to prove that the species obtained from Guangxi is a new distribution of Th. corticale .